Assessment of the Impacts of Climate Change on Maize Production in the Southern and Western Highlands Sub-agro Ecological Zones of Tanzania - Luhunga, Philbert M. (Frontiers in Environmental Science, 2017)
The Intergovernmental Panel on Climate Change (IPCC) fourth assessment report confirmed that climate change is unequivocal. It is coming to us faster with larger impacts and bigger risks than even most climate scientists expected as recently as a few years ago. One particular worry is the disastrous consequence to agriculture and food security sectors in many parts of the world, particularly in developing countries. Adaptation is the only option to reduce the impacts of climate change. However, before planning adaptation policies or strategies to climate change, it is important to assess the impacts of climate change at regional and local scale to have scientific evidence that would guide the formulation of such policies or strategies. In this study the impacts of climate change on rain-fed maize (Zea Mays) production in the southern and western highlands sub-agro ecological zones of Tanzania are evaluated. High resolution climate simulations from the Coordinated Regional Climate Downscaling Experiment_Regional Climate Models (CORDEX_RCMs) were used as input into the Decision Support System for Agro-technological Transfer (DSSAT) to simulate maize yield in the historical climate condition (1971–2000), present (2010–2039), mid (2040–2069), and end (2070–2099) centuries. Daily rainfall, solar radiations, minimum and maximum temperatures for the historical (1971–2000) climate condition and future climate projections (2010–2099) under two Representative Concentration Pathways (RCPs) RCP4.5 and RCP 8.5 were used to drive DSSAT. The impacts of climate change were assessed by comparing the average maize yields in historical climate condition against the average of simulated maize yields in the present, mid and end centuries under RCP4.5 and RCP8.5. Results of future maize yields estimates from DSSAT driven by individual RCMs under both RCP scenarios (RCP 4.5 and RCP 8.5) differs from one RCM to another and from one scenario to another. This highlight the uncertainty associated with the projection. Results from the ensemble average of the yields indicated that maize yields will decline in future climate condition by 3.1 and 5.3% under RCP 4.5 and RCP8.5, respectively. High decreases in maize yield of 9.6% are expected in the end centuries under RCP 8.5. The main reason for decline in maize yields during future climate is the increase in temperatures that will shorten the length of growing seasons. Seasonal minimum temperature and maximum temperature are expected to increase by 1.84 and 1.53°C, respectively under RCP 4.5 and by about 2.72 and 2.2°C, respectively, under RCP 8.5. Therefore it is recommended that more studies need to be carried, especially by crop breeders to find maize varieties that can withstand the impacts of increased temperatures over southern and western highlands sub-agro ecological zones of Tanzania.